INTERSUBJECT COMMUNICATIONS OF LITERATURE AND CHEMISTRY IN THE PERIODIC SYSTEM - Nazhikanova, D.A.; Kenshinbek, Zh.B. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
In the article, the possibilities of the implementation of interdisciplinary relations in the course of studying chemistry and literature are considered. This article emphasizes the importance and benefits of combining chemistry with poetry. The implementation of intersubject communications in the practice of learning involves the cooperation of a chemistry teacher with teachers of other subjects.
Keywords: poetry; views; lesson development; cultural thought; history of the periodic table; intersubject communications; education; periodic table of D.I. Mendeleev; gate of chemistry